Desain Sistem Monitoring dan Penyiraman Tanaman Tomat Berbasis Internet of Things (IoT) - Zulhijayanto -; Abdul Fadlil (Universitas Ahmad Dahlan, 2022)
Air temperature and soil moisture are things that need to be considered in caring for tomato plants. Watering is also important because tomatoes are plants that do not tolerate dry soil. This study aims to monitor air temperature, air humidity and soil moisture as well as watering plants when the soil moisture value is dry. The research method used is IoT-based watering automation with Node MCU components ESP8266, DHT11 sensor, V1.2 SEN0193 capacitive soil moisture sensor, 1 channel relay module, DC water pump, and 20x4 LCD. The test results of the DHT11 sensor on air temperature have an error of 3.09% with an accuracy of 96.91%. The error value for air humidity is 12.34% with an accuracy of 87.61%. The V1.2 SEN0193 capacitive soil moisture sensor has an error of 6.82% with an accuracy of 93.18%. This research has succeeded in watering plants based on the specified value, which is below 60% and stops watering before 80%. Suhu udara dan kelembaban tanah adalah hal yang perlu diperhatikan dalam merawat tanaman tomat. Penyiraman juga penting karena tomat adalah tanaman yang tidak tahan terhadap tanah yang kering. Penelitian ini bertujuan untuk memantau suhu udara, kelembaban udara dan kelembaban tanah serta menyiram tanaman pada saat nilai kelembaban tanah kering. Metode penelitian yang digunakan adalah otomasi penyiraman berbasis IoT dengan komponen Node MCU ESP8266, sensor DHT11, sensor kelembaban tanah kapasitif V1.2 SEN0193, modul relay 1 channel, pompa air DC, dan LCD 20x4. Hasil pengujian sensor DHT11 terhadap suhu udara memiliki error sebesar 3,09 % dengan akurasi 96,91%. Nilai error terhadap kelembaban udara sebesar 12,34 % dengan akurasi 87,61%. Pada sensor kelembaban tanah kapasitif V1.2 SEN0193 memiliki error sebesar 6.82 % dengan akurasi 93,18%. Penelitian ini telah berhasil menyiram tanaman berdasarkan nilai yang ditentukan yaitu di bawah 60% dan berhenti menyiram sebelum 80%.